(untitled) (Revista INTEREDU11, 2024)
Education, a phenomenon that has blessed man, today curses him. The bureaucratic, linear and predictive nature of curricula is a rope around the neck for learning, supplanting it with representative formalizations and ignoring the radicality, complexity and contingency involved in its execution. For this reason, both teachers and students today suffer from education, running after the pre-established curricular time, unintentionally, also running away from learning. For these reasons, the present topic aims to understand the state of the learning phenomenon in educational institutions, from a functional and structural analysis of these, from the theoretical perspective of Niklas Luhmann’s social systems. The methodology with which this subject is approached is bibliographic, deductive, and descriptive in nature, since, from different sources and theories, institutionalized education is analyzed in order to describe it interpretatively. The idea defended in this text is that learning is a non-primary issue in institutionalized education, remaining in the background, succumbed by the binary code that governs the institutions and embodied only in curricular representations that do not validate that learning is something contingent and erected in complexity, which only if negotiated, can achieve full attainment in students.